Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Return On Equity Pada PT Unilever Indonesia Tbk Periode 2012 -2022 - Shela Fadila Sari; Siti Nurcahayati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the influence of the Current Ratio, Debt To Equity Ratio on Return On Equity at PT Unilever Indonesia Tbk 2012 - 2022. The method used in this research is quantitative research. The population used in this research is the financial report of PT Unilever Indonesia Tbk. The sample data used by the author in this research are financial reports in the form of the balance sheet and profit and loss report of PT Unilever Indonesia Tbk for the period 2012 - 2022. The results of this research show that there is no significant influence of the Current Ratio on Return On Equity at PT Unilever Indonesia Tbk. 2012 – 2022 as evidenced by the tcount value of 0.081 < ttable 2.306 with a significance level of 0.938 > 0.05. There is no significant influence between Debt To Equity on Return On Equity of PT Unilever Indonesia Tbk for the 2012 - 2022 period as evidenced by the t value of 2,265 < t table 2,306 with a significance level of 0.053 > 0.05. Together (simultaneously), the Current Ratio and Debt To Equity Ratio variables have a significant effect on Return On Equity at PT Unilever Indonesia Tbk for the 2012 - 2022 period as evidenced by the Fcount value of 5.658 > Ftable 4.46 with a significance level of 0.029 < 0.05. The coefficient of determination is 58.6% while the remaining 41.4% is influenced by other variables.